The National Fauna Selection - Antin Siswantinah Wibowo (Media Konservasi, 1996)
The objectives of the National Fauna Selection were promoting living resources as national identity,conservation awareness and national rightfully proudness. The result show that (1) The selection has been involved stake holder transparantly, (2) and done scientifically, (3) The National Fauna Selection Policy is in theframework of biodiversity comervation program and should be made use for hiodiversity conservation effort.